Neonatal Chest Wall Rhabdomyosarcoma - Feldman, Michael; Steiner, Zvi; Groisman, Gabriel; Nadir, Erez (European Journal of Pediatric Surgery Reports, 2015)
An infant was born at term with a huge chest mass diagnosed as rhabdomyosarcoma. Treatment consisted of surgical resection and chemotherapy. We describe this very rare congenital mass and the problematic therapeutic management of such a tumor in a newborn.
Keywords: rhabdomyosarcoma; newborn; chest wall; tumor